ECOLOGICAL RESTORATION IN NATURAL CONSERVATION TOURISM AREA - Sulis Purwanto (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2019)
Ecotourism is a concept of tourism development that pays attention to the physical, economic and sociocultural environment and provides positive benefits to local communities and tourist experience. The concept of ecotourism that can be applied in national park areas is ecological restoration. This study aims to determine the application of ecological restoration in nature-based tourism areas. The method used is descriptive qualitative by conducting observations, interviews and literature studies. The results show that ecological restoration is part of the concept of ecotourism that can be applied in the national park area. Ecological restoration is the most important part of ecotourism development. Examples of the application of ecological restoration in the area of Mount Merapi is by replanting trees after eruption and conservation of water. Ecological restoration is carried out to improve the quality of the damaged nature in accordance with its original state and can also support tourism areas around the National Park of Mount Merapi such as Tlogo Muncar, Goa Japan and Plawangan Turgo Hill.